Penerapan Hukum Terhadap Pelaku Tindak Pidana Penipuan Yang Dilakukan Secara Bersama-Sama (Studi Putusan Nomor : 1287/Pid.B/2018/PN.MDN) - Nanda Rafina; Ridho Mubarak; M Yusrizal Adi Saputra (Universitas Medan Area, 2021)
The application of the law against the perpetrators of fraud committed jointly in decision number: 1287 / Pid.B / 2018 / PN.MDN, it can be seen that fraud is a crime that often occurs in everyday life, fraud crimes can be committed. individually or collectively called deelneming. The type of research used is juridical normative and analytical descriptive research characteristics and for data collection used library research and field research. analysis of the problem is carried out by the qualitative method. Application of Law Against Fraud Crime Conducted Together in Decision Number: 1287 / Pid.B / 2018 / PN. MDN, the prosecutor charged the defendant with the first indictment contained in the indictment, namely in Article 378 of the Criminal Code in conjunction with Article 55 of the Criminal Code and the judge made several considerations by making a verdict against the defendant in accordance with the demands filed by the public prosecutor. Judges' considerations in making a decision on Decision number: 1287 / Pid.B / 2018 / PN.MDN have been done as well as possible, the judge made several considerations where the judge's consideration was in accordance with the demands of the Public Prosecutor and before passing the judge's decision also took into account the burdensome circumstances and which relieves the defendant and in order to impose a sentence on this decision the judge has made prior considerations, by providing certainty and justice in making the decision it will create benefits for both the defendant and the victim.